Kebijakan Dana Kampung dan Budaya Organisasi Dalam Mendukung Kinerja Aparatur Kampung - Muhammad Aryo Widiyoko (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2021)
This study aims to determine and analyze the effect of implementing village fund policies and organizational culture on the performance of village officials. This research is explanatory and associative. The scope variables in this study consist of the implementation of village policies and organizational culture as independent variables and the village apparatus's performance as the dependent. The population in this study were all village officials in Sorong Regency, as many as 2,486 people. The sampling technique used is the Slovin sampling formulation using 100 respondents. The data collection method used a questionnaire with a Likert scale. The analysis technique used is multiple linear regression. The research results in this study are: (1) the implementation of the village fund policy partially has a significant effect on the performance of the village apparatus, (2) the organizational culture partially has a significant effect on the performance of the village apparatus. Village apparatus, (3) implementation of village fund policy Simultaneous organizational and village culture have a significant effect on the performance of village officials.